Pemberdayaan Perempuan Melalui Pemanfaatan Sampah Pada Bank Sampah Induk Dalang Collection Kota Pekanbaru - Tri Melisa Selviani; Sunarto Sunarto (Cakrawala Repositori IMWI, 2023)
Empowering women is a priority for the government for sustainable development. Referring to the 2030 Sustainable Development Goals (SDGs), women's empowerment is an important component in realizing it, then environmental issues are also a topic that needs to be discussed. Regarding this the government's idea is presenting a waste bank, the concept was instead of saving the environment, it also helps the community's economy through empowerment. The purpose of this study is to see the empowerment communication model used and to determine the level of equality based on Sara Longwe's gender analysis. This study uses a qualitative approach with descriptive methods with data sources obtained from in-depth interviews and observations. The results showed that the empowerment communication model used by the Dalang Collection in its implementation was the innovation diffusion empowerment communication model. And for the results of the analysis of the level of equality of women's empowerment, the first level is the welfare and the second level, is access. However, in terms of awareness and control, it was not achieved and for the participation, it can be said that it has almost been achieved.